PEMBUATAN BIOBRIKET TANDAN KOSONG KELAPA SAWIT DAN TEMPURUNG KELAPA SEBAGAI SUMBER ENERGI ALTERNATIF RAMAH LINGKUNGAN - Herlina Anggriani Marbun; Giyanto; Hardiansyah Sinaga (Jurnal Agro Fabrica, 2019)
Fluctuations in fuel prices stimulate efforts to find alternative energy that is environmentally friendly. The processing of oil palm plantations produces waste or quite a lot of products ± 23% of the weight of fresh fruit bunches. Utilization of Palm Empty Fruit Bunch (PEFB) as biobriquettes was chosen in this study by mixing other ingredients, namely coconut shell. The treatment in the study was the composition of the mixture of PEFB and shell PEFB-1, PEFB-2, PEFB-3, PEFB-4 and PEFB-5 with a ratio of weight (100% -0%), (75% -25%), (50% -50%), (25% -75%) and (0% -100%). The research was carried out in Medan STIPAP, ITM Laboratory and PTKI Alboratorium in April - September 2018. Observation parameters were heating value, water content, ash content, density, compressive strength and combustion rate. The results showed that briquettes with dominant PEFB material, PEFB-1 and PEFB-2, produced less quality biobriquettes, especially low calorific value. The best treatment is PEFB-4 (25% EFB and 75% shell) with characters that appropriate to the specifications of the quality standard of charcoal briquettes.